Addressing Challenges in Evaluating School Principal Improvement Efforts - Burkhauser, Susan (RAND Corporation, 2012)
Given the focus on accountability in education, stakeholders are interested in evaluating whether efforts aimed at improving school leadership show results; the key criteria are student outcomes. This report describes challenges that states, districts, and other entities can expect to encounter as they evaluate efforts targeting school leadership as a way to improve student outcomes and offers suggestions for dealing with those challenges.